Konstruksi Realitas Peran Anak Perempuan dalam Keluarga Batak di Film Ngeri-Ngeri Sedap - Jaya, Daniel Putra; Winduwati, Septia (Kiwari, 2025)
This study examines the construction of the reality of the role of daughters in Batak families as depicted in the film Ngeri-Ngeri Sedap. In Batak culture, women hold significant roles within the family, although their position is often viewed through traditional customs that place men in dominant roles. The film Ngeri-Ngeri Sedap incorporates several social ideologies, including feminism, gender equality, patriarchy, and patrilineality. This research aims to provide insights into the meaning and constructed reality of the role of daughters in Batak families as portrayed in Ngeri-Ngeri Sedap. It employs theories of mass communication, reality construction, gender equality, and feminism, enriched by Roland Barthes' semiotics analysis method, which consists of three components: denotation, connotation, and myth. To gather data, the researcher utilized semiotic analysis to identify the meanings and symbols present in the film Ngeri-Ngeri Sedap and further explored these findings through interviews with expert informants to strengthen the research results. The findings reveal forms of feminism and patriarchy experienced by women in Batak families, as depicted through the scenes in the film Ngeri-Ngeri Sedap. Penelitian ini membahas konstruksi realitas peran anak perempuan dalam keluarga Batak di Film Ngeri-Ngeri Sedap. Dalam budaya Batak, perempuan memiliki peran penting dalam keluarga, meskipun posisi mereka sering dilihat melalui perspektif adat yang menempatkan laki-laki dalam peran dominan. Film Ngeri-Ngeri Sedap menyisipkan beberapa ideologi sosial seperti feminisme, kesetaraan gender, patriarki, dan patrilineal. Penelitian ini bertujuan untuk memberikan gambaran mengenai konstruksi realitas peran anak perempuan dalam keluarga Batak di film Ngeri-Ngeri Sedap. Penelitian ini menggunakan teori komunikasi massa, konsep konstruksi realitas, kesetaraan gender, feminisme, dan diperkaya dengan metode analisis semiotika Roland Barthes, yang terdiri dari tiga komponen yaitu denotasi, konotasi, dan mitos. Dalam memperoleh data, peneliti menggunakan analisis semiotika untuk memperlihatkan makna atau simbol yang ada dalam film Ngeri-Ngeri Sedap dan diperdalam dengan melakukan wawancara oleh narasumber ahli Kebudayaan Batak untuk memperkuat hasil penelitian ini. Hasil penelitian menunjukkan temuan berupa bentuk-bentuk feminisme dan juga patriarki yang dialami perempuan dalam keluarga Batak yang digambarkan melalui adegan-adegan dalam film Ngeri-Ngeri Sedap.